11x-76=6x-6

Simple and best practice solution for 11x-76=6x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-76=6x-6 equation:


Simplifying
11x + -76 = 6x + -6

Reorder the terms:
-76 + 11x = 6x + -6

Reorder the terms:
-76 + 11x = -6 + 6x

Solving
-76 + 11x = -6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-76 + 11x + -6x = -6 + 6x + -6x

Combine like terms: 11x + -6x = 5x
-76 + 5x = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
-76 + 5x = -6 + 0
-76 + 5x = -6

Add '76' to each side of the equation.
-76 + 76 + 5x = -6 + 76

Combine like terms: -76 + 76 = 0
0 + 5x = -6 + 76
5x = -6 + 76

Combine like terms: -6 + 76 = 70
5x = 70

Divide each side by '5'.
x = 14

Simplifying
x = 14

 

You can always share this solution

See similar equations:

| (x-11)(x-11)=0 | | 4x+2+3x=2+3+2x | | a=5(x-3)-2x(x-3) | | (7-2y)(5+y)= | | 2ac-4ad+6bc-12bd=0 | | (x+2)(2x-1)= | | 7+z=8z-13 | | 3y-7= | | 8x^2+32x+24=0 | | 9p^2+30p+25=0 | | 4(x-4)=2x+2 | | X-(35-X)=5 | | 8x^2+71x-9=0 | | b+3(y+3b)= | | x^4+13x^2+30=0 | | x-35-x=5 | | x^4+13x+30=0 | | 125a^3+64b^3=0 | | 12x^2-37x+28=0 | | 8x-54=4x-6 | | 8x^2+16x-23=0 | | 7+2x=x+10 | | 4(t-3)+8t=6t(2t+2)-8 | | 4x^2-5=55 | | x+(x+25)+(2x-28)=577 | | 8(x-9)+4=8x+6 | | 5m^2-20mn-60n^2=0 | | 3(x+3)=5(1-x)-1 | | 7x+3=3x-17 | | 8x^3-3x^2+5x+15=0 | | 12(n+6)=3(24+4n) | | 8x^3-3x^2+5x+5=0 | | 3+4y-2=8y+13-2y | | -2x+25=-9 | | .5x-18=1.2x-25 | | 5n=7n-12 | | 9t+13t=132 | | -10.3x=61.8 | | y=2x^2+6x-5 | | 3t=57 | | 4x+13=-29-10x | | 14.1*8.4= | | 3000=x*50 | | (9+x)+(6+x)+(3+x)=(4+x*2)+(1+x*2) | | a=(14.1)(8.4)/2 | | a=(14.1)(8.4)/.5 | | a=1/2(14.1)(8.4) | | 3x+36=12x-72 | | -(7y+3)-(-6y-6)=-4 | | 12+7m=m-6 | | 14-5m=3m | | 9x-4=103 | | z+36=16 | | C=14(3.14) | | (8y*-7y+3)-(6y*-7y+9)= | | 7y+21=0 | | 4x^3+39x^2=0 | | 5+x=7(x+3) | | w+6+s-6=380 | | 162-2x^4=0 | | Y=-X^3+6X^2-9X-10 | | x^4+5x^3-2x-10=0 | | 0.4x-3=0.1(x+30) | | -26=d-7 | | 1.4(2x-3)-1=-10.6+2.8x+5.4 |

Equations solver categories